Sosialisasi Pencegahan Bahaya Bullying pada Siswa SMPN I Kuta Makmur - Russy Ranggayoni; Yusra; Nisrina; Rahmiaty (LSM Catimore dan Sahabat, 2023)
Bullying behavior is an issue that is often discussed today. This behavior is often found in environments that are not supposed to be, such as in the school and family environment. Bullying behavior is an aggressive or violent action that can lead to conflict between the perpetrator and the victim. This community service activity is an act of outreach that aims to provide education and to prevent the students so they don't commit acts of bullying within the school environment or outside the school environment. The method used in this activity is in the form of giving material in the form of lectures and questions and answers. The results of socialization activities show that students are very motivated in the activity process and can understand the material and information conveyed by the speakers. The implication of this activity is that students are aware of the negative impact of bullying behavior and are responsible for efforts to prevent this behavior in their daily environment.